Wooden jali work on corridors - Ghosh, Ayan (Jio Institute, 2023)
Externally placed pipes drain rainwater from the roofs during the monsoon season. The pierced wooden jalis allow for the play of light and shade in the corridors of the building. They were made by Telugu-speaking craftsmen at the JJ School of Art and were meant to provide shade during summer months and protect the corridors from rain and sunlight.